The Influence of Service Quality and Patient Experience on Inpatient Satisfaction - Rosilawati Rosilawati; R. Rina Novianty Ariawaty; Rukhiyat Syahidin (Newinera Publisher, 2025)
This study aims to analyze the influence of service quality and patient experience on inpatient satisfaction at Dr. Abdul Aziz Regional General Hospital, Singkawang. A quantitative approach was used, with a survey of 165 respondents. Service quality was categorized as good (score 3.7), particularly in the dimensions of reliability, assurance, empathy, and responsiveness. However, the physical evidence dimension was categorized as fair. Patient experience was rated as good (score 3.5), particularly in the hospital environment dimension. Specifically, the dimensions of pain management, medication communication, and discharge information were categorized as fair and need improvement. Patient satisfaction with the implementation of the code of ethics for professional service standards was rated as good, while the implementation of health service standards was categorized as fair. Statistical analysis showed that both service quality (β = 0.510; t = 7.515; Sig. 0.000) and patient experience (β = 0.382; t = 5.633; Sig. 0.000) had a positive and significant effect on patient satisfaction. Service quality had the most dominant influence on patient satisfaction. Therefore, comprehensive and continuous improvement in service quality is highly recommended to optimally enhance patient satisfaction.